KUALITAS PROGRAM ‘INDONESIAKU’ DI TRANS7 DALAM MENERAPKAN PEDOMAN PERILAKU PENYIARAN DAN STANDAR PROGRAM SIARAN (P3SPS) - Tampubolon, Parulian; Silviani, Irene; Khairullah, Khairullah (JURNAL PROINTEGRITA, 2020)
This journal is entitled "The Quality of 'My Indonesia' Program at TRANS7 in Applying the Code of Conduct for Broadcasting and Broadcast Program Standards (P3SPS)". This study focuses on exploring the program in implementing P3SPS. This study uses the constructivism paradigm as an approach. In this study, researchers interviewed several research subjects who were monitors of broadcast content at the Regional Indonesian Broadcasting Commission of North Sumatra Province (KPID-SU). In this research, the results show that the 'Indonesiaku' program has quality in implementing P3SPS in the aspects of public interest, public services, broadcast program classification, journalistic principles, interviewers and language. However, on the aspect of journalistic principles, there are still editions that do not make corrections to the local government regarding problems that occur in the field. The input for P3SPS is to regulate broadcasts featuring unlicensed traditional health service providers, but this is a reality and a blurry portrait of the difficulty of access to health in this country